Antibiotic resistance and the presence of blaCfxA and blaCSP genes in β-lactamase-producing clinical Capnocytophaga isolates from a university hospital in Japan. Issue 10 (20th October 2021) - Matsumoto, Takehisa; Matsumoto-Matsubara, Miki; Horiuchi, Kazuki; Arai, Eriko; Negishi, Tatsuya; Natori, Tatsuya; Kawakami, Yoshiyuki
Abstract : Introduction . Capnocytophaga species are common inhabitants of the oral cavity and can be responsible for systemic diseases in immunocompromised patients with granulocytopenia. Furthermore, it has been reported that some clinical isolates of Capnocytophaga species produce extended-spectrum β-lactamases (ESBLs). Gap statement. Information is lacking about the types of β-lactamase genes possessed by Capnocytophaga spp. and the antimicrobial susceptibility of Capnocytophaga spp. possessing each β-lactamase gene. Aim. The aim of this study was to investigate the presence of β-lactamase genes in clinical strains of β-lactamase-producing Capnocytophaga species isolated from clinical samples acquired at Shinshu University Hospital and examine the antimicrobial susceptibility of those strains. Methodology. The β-lactamase-producing Capnocytophaga species ( n =49) were obtained from clinical specimens. PCR assays were used to detect bla CfxA, bla CSP, bla TEM, bla CepA/CblA and transposon Tn 4555 genes. Southern hybridization assays were used to detect bla CfxA and bla CSP . The minimum inhibitory concentration of some β-lactams was determined using the E-test method. Results. PCR analysis indicated that the bla CfxA gene was present in 15 (30.6 %) and the bla CSP gene in 35 (69.3 %) of the 49 Capnocytophaga strains investigated, . Both bla CfxA and bla CSP genes were detected in a Capnocytophaga gingivalis strain. The PCR results were confirmed by Southern hybridization assays. Transposon Tn 4555 was only detected in Capnocytophaga spp. harbouring the bla CfxA gene. All the β-lactamase-producing Capnocytophaga isolates were susceptible to ceftazidime–clavulanic acid, cefoxitin and imipenem. In contrast, most of the isolates were resistant to amoxicillin. Conclusions. The clinical isolates of Capnocytophaga spp. showed a high prevalence of the bla CSP gene in Japan. The presence of the bla CSP gene was distributed in Capnocytophaga sputigena as well as other Capnocytophaga spp. These results seem to suggest the dissemination of bla CfxA and bla CSP β-lactamase genes among Capnocytophaga species.